2009
DOI: 10.1534/genetics.109.103614
|View full text |Cite
|
Sign up to set email alerts
|

The Cation Diffusion Facilitator Gene cdf-2 Mediates Zinc Metabolism in Caenorhabditis elegans

Abstract: Zinc is essential for many cellular processes. To use Caenorhabditis elegans to study zinc metabolism, we developed culture conditions allowing full control of dietary zinc and methods to measure zinc content of animals. Dietary zinc dramatically affected growth and zinc content; wild-type worms survived from 7 mm to 1.3 mm dietary zinc, and zinc content varied 27-fold. We investigated cdf-2, which encodes a predicted zinc transporter in the cation diffusion facilitator family. cdf-2 mRNA levels were increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
97
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(101 citation statements)
references
References 67 publications
2
97
0
Order By: Relevance
“…By using inductively coupled plasma-mass spectrometry (ICP-MS) to measure total zinc content in worm extracts, we demonstrated that C. elegans cultured with high dietary zinc display elevated levels of total zinc, suggesting excess zinc is stored (Davis et al, 2009). To identify the site of zinc storage, we used zinc-specific fluorescent dyes to visualize zinc.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By using inductively coupled plasma-mass spectrometry (ICP-MS) to measure total zinc content in worm extracts, we demonstrated that C. elegans cultured with high dietary zinc display elevated levels of total zinc, suggesting excess zinc is stored (Davis et al, 2009). To identify the site of zinc storage, we used zinc-specific fluorescent dyes to visualize zinc.…”
Section: Resultsmentioning
confidence: 99%
“…To study zinc metabolism, we developed methods to manipulate dietary zinc and used forward and reverse genetic approaches to identify genes important for zinc metabolism (Bruinsma et al, 2008; Davis et al, 2009; Murphy et al, 2011). C. elegans contains highly conserved families of CDF, ZIP and metallothionein genes, suggesting that fundamental mechanisms of zinc metabolism may be similar to other animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, we utilized C. elegans, which has been widely used in the study of the metabolism of other metals, including iron, heme, and zinc (8,(13)(14)(15)(16)(17). Although mammals have two copper exporters, serving complementary functions in different tissues such as the gut and liver, lower metazoans (including nematodes (C. elegans) and insects (Drosophila melanogaster)) have only a single homolog of ATP7A/B (2,18,19).…”
mentioning
confidence: 99%
“…8 To identify genes involved in this type of stress resistance, Bruinsma et al (2008) performed a forward genetic screen for worms that are resistant to the toxicity caused by high levels of dietary zinc and isolated 2 mutations in natc-1. 9 Warnhoff et al (2014) identified the affected gene by positional cloning and demonstrated that the natc-1(am138) and natc-1 (am134) mutations cause a strong loss-offunction.…”
Section: Introductionmentioning
confidence: 99%